What Drives Students’ Intention to Use Islamic Banking Services? Evidence From a SEM-PLS Analysis - Ridwan Alamsyah; Alya Azhana Maulidha; Muhamad Tanzi Maulana; Berakon, Izra (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
The development of Islamic banking in Indonesia continues to grow however, the level of adoption among university students remains relatively limited. This phenomenon is particularly evident among students of the Faculty of Islamic Economics and Business (FEBI), who formally study Islamic economics and finance but do not necessarily use Islamic banking services in their daily financial activities. Understanding the factors that drive students’ intention to use Islamic banking services is therefore essential to support the expansion of the Islamic banking industry. This study aims to analyze the determinants influencing the intention of FEBI students to use Islamic banking services. A quantitative approach was employed using Partial Least Squares–Structural Equation Modelling (PLS-SEM), with data collected from FEBI students through a structured questionnaire. The results indicate that perceived ease of use has a significant effect on students’ intention to use Islamic banking services, while perceived usefulness, trust, social influence, and switching cost do not show significant effects. These findings suggest that ease of use plays a crucial role in encouraging FEBI students to adopt Islamic banking services. The study provides practical implications for Islamic banks to prioritize the development of user-friendly and accessible services to attract young consumers, particularly those with an academic background in Islamic economics and finance.